Pelatihan dengan Menggunakan Metode Pembelajaran Berdiferensiasi di Sekolah Dasar - Yanti Yandri Kusuma; Nurhaswinda; Iis Aprinawati; Tedi Susanto; Nuraina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
From this community service activity, it can be concluded that the Dissemination of Independent Curriculum Learning was carried out to welcome the new school year, where Sekolah Dasar Pahlawan is one of the schools that will implement the independent curriculum with changing independent choices. Principals and teachers at educational units that will implement the independent curriculum with changing independent choices must utilize the teaching tools available in the Independent curriculum learning. The dissemination activity was carried out with two materials, namely Differentiated Learning and Numeracy Literacy; presentation and discussion of Independent Curriculum Learning; and Follow-up Plan. In the presentation and discussion activities on Independent Curriculum Learning, the features and problems experienced by teachers were discussed. Dissemination of Independent Curriculum Learning is very important for teachers whose schools will implement the independent curriculum.